Experimental investigation of the flexure impact properties of glass fiber reinforced polymer composites - Nurul Ain Nabihah, Abd Rahman (2017)
A polymer composite is a plastic material come from two or more material with different chemical properties. In this paper, is proposed to determine the flexure and impact properties of glass fiber reinforced polymer composites. The properties of fiber reinforced polymer composite depend on properties of fiber and resin and the ratio of fiber-resin (fiber volume fraction). The first objective was to prepare and fabricate the specimen with four different compositions of polypropylene, nylon and glass fiber in a composite. To investigate the impact strength of composites, Izod impact test were conducted following the standard of ASTM D4813 while flexure strength was determined using three-point bending test according to ASTM D790. The mechanical properties of fiber reinforced polymer composite were improved remarkably by adding the glass fiber percentage. Based on the result, the increase percentage of glass fiber in composite, it gives the good flexure strength on material but it is not good in impact strength. The fractured specimens for impact test have undergone the microstructure analysis by using the optical microscope.